2022
DOI: 10.1007/s12665-022-10331-x
|View full text |Cite
|
Sign up to set email alerts
|

Ecotourism risk assessment in Yaoluoping Nature Reserve, Anhui, China based on GIS

Abstract: As tourism development and human disturbance increase, they have been affecting the functional structure distribution, sustainable utilization of resources, and ecological benefits of nature reserves. At the same time, ecological risk has increased significantly. This study proposes ecotourism development patterns for risk areas at each level, to provide a basis for stabilizing and promoting the ecological sustainable development of nature reserves. Yaoluoping National Nature Reserve in China is used as a stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…For example, in a study on the Yaoluoping Nature Reserve in the Anhui Province of China, except for the lowest-risk area, the ecological risk level in the core zone was the lowest, whereas other levels of ecological risk in the core zone of the Yaoluoping Nature Reserve were greater than those in the buffer zone; furthermore, the levels of medium and medium-high ecological risk in the buffer zone were greater than those in the experimental zone. This research suggested that the ecological risks in the core zone and buffer zone are not optimistic [38]. Although the core zone of the Lushan National Nature Reserve is not at the highest level of risk, the higher-risk area accounted for 9.71% of the core zone, with the medium-risk area accounting for 28.97%.…”
Section: Ecological Risk Of the Nature Reservementioning
confidence: 87%
See 1 more Smart Citation
“…For example, in a study on the Yaoluoping Nature Reserve in the Anhui Province of China, except for the lowest-risk area, the ecological risk level in the core zone was the lowest, whereas other levels of ecological risk in the core zone of the Yaoluoping Nature Reserve were greater than those in the buffer zone; furthermore, the levels of medium and medium-high ecological risk in the buffer zone were greater than those in the experimental zone. This research suggested that the ecological risks in the core zone and buffer zone are not optimistic [38]. Although the core zone of the Lushan National Nature Reserve is not at the highest level of risk, the higher-risk area accounted for 9.71% of the core zone, with the medium-risk area accounting for 28.97%.…”
Section: Ecological Risk Of the Nature Reservementioning
confidence: 87%
“…The results of the ecological risk assessment almost indicated that the ecological risks of nature reserves are all at a relatively low level. According to a study by Tang et al [38], which focused on the Yaoluoping Nature Reserve in the Anhui Province of China, the ecological risks of nearly 90% of the area were at a medium or low level. Wang et al [39] found that the proportion of the Baishuijiang National Nature Reserve comprising the lowest-risk and lower-risk areas was 97%.…”
Section: Ecological Risk Of the Nature Reservementioning
confidence: 99%
“…The other is based on the landscape index method to quantitatively evaluate and describe the overall quality and spatial-temporal differentiation characteristics of regional ecological risk [21,22]. These two evaluation methods have been widely used in the research scope of watersheds [23,24], administrative units [25,26], mining areas [27] and nature reserves [28,29]. The former approach focuses on the identification of risk sources and risk receptors.…”
Section: Introductionmentioning
confidence: 99%